Pemanfaatan Media Pendidikan di Polandia dan Indonesia - Hasibuan, Budi Azhari Muda; Siregar, Royhanun (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to examine the use of educational media in Poland and Indonesia by employing a literature review method. This method involves the exploration and analysis of various written sources such as scholarly articles, policy reports, and relevant educational documents from both countries. Poland and Indonesia are countries with a history of colonization, yet they currently display different developments in their educational systems. Poland is known as one of the countries with a high-quality education system, which is partly demonstrated through the optimal use of educational media. The availability of evenly distributed infrastructure and good technology integration are the main supporting factors in achieving this. Meanwhile, Indonesia still faces challenges in equal access to educational media, especially in areas that do not have adequate educational infrastructure. This study shows that the utilization of educational media greatly influences the effectiveness of the teaching and learning process. The results of this study are expected to provide insights and inputs for the development of education policies in Indonesia, particularly in improving the more equitable and efficient utilization of educational media